Предмет: Алгебра,
автор: Aneliaa17
!!! Помогите решить систему. На фото. Сама никак...
Приложения:
Ответы
Автор ответа:
1
25t = x( t - 1 )
x = 25t / ( t - 1 ) ; t ≠ 1
-------------------------------------------------------------
25( t + ( 1/6 )) = 3/4x( t + ( 1/6 ) - 1 )
25( ( 6t + 1 ) / 6 ) = 3/4x( ( 6t - 5 ) / 6 )
( 100( 6t + 1 )) / 24 = ( 3x( 6t - 5 ) ) / 24
100( 6t + 1 ) = 3x( 6t - 5 )
100( 6t + 1 ) = ( 75t / ( t - 1 )) * ( 6t - 5 )
100( 6t + 1 ) = ( 75t( 6t - 5 )) / ( t - 1 )
600t + 100 = ( 450t^2 - 375t ) / ( t - 1 )
450t^2 - 375t = ( t - 1 )( 600t + 100 )
450t^2 - 375t = 600t^2 + 100t - 600t - 100
450t^2 - 375t = 600t^2 - 500t - 100
150t^2 - 125t - 100 = 0
1,5t^2 - 1,25t - 1 = 0
D = 1,5625 + 6 = 7,5625 = 2,75^2
t1 = ( 1,25 + 2,75 ) : 3 = 4/3 = 1 1/3
t2 = ( 1,25 - 2,75 ) : 3 = - 1,5 : 3 = - 0,5
x = 25t / ( t - 1 )
x1 = (25*(4/3)) / ( 1 1/3 - 1 ) = 100/3 *1/3 = 100/9 = 11 1/9
x2 = ( 25*(- 0,5 )) / ( - 0,5 - 1 ) = ( - 12,5 )*( - 1,5 ) = 18,75
x = 25t / ( t - 1 ) ; t ≠ 1
-------------------------------------------------------------
25( t + ( 1/6 )) = 3/4x( t + ( 1/6 ) - 1 )
25( ( 6t + 1 ) / 6 ) = 3/4x( ( 6t - 5 ) / 6 )
( 100( 6t + 1 )) / 24 = ( 3x( 6t - 5 ) ) / 24
100( 6t + 1 ) = 3x( 6t - 5 )
100( 6t + 1 ) = ( 75t / ( t - 1 )) * ( 6t - 5 )
100( 6t + 1 ) = ( 75t( 6t - 5 )) / ( t - 1 )
600t + 100 = ( 450t^2 - 375t ) / ( t - 1 )
450t^2 - 375t = ( t - 1 )( 600t + 100 )
450t^2 - 375t = 600t^2 + 100t - 600t - 100
450t^2 - 375t = 600t^2 - 500t - 100
150t^2 - 125t - 100 = 0
1,5t^2 - 1,25t - 1 = 0
D = 1,5625 + 6 = 7,5625 = 2,75^2
t1 = ( 1,25 + 2,75 ) : 3 = 4/3 = 1 1/3
t2 = ( 1,25 - 2,75 ) : 3 = - 1,5 : 3 = - 0,5
x = 25t / ( t - 1 )
x1 = (25*(4/3)) / ( 1 1/3 - 1 ) = 100/3 *1/3 = 100/9 = 11 1/9
x2 = ( 25*(- 0,5 )) / ( - 0,5 - 1 ) = ( - 12,5 )*( - 1,5 ) = 18,75
Aneliaa17:
Спасибо тебе
Похожие вопросы
Предмет: Физика,
автор: bonniesss
Предмет: Математика,
автор: qwwdanaengel
Предмет: География,
автор: alinkadybovuc25
Предмет: Биология,
автор: imozaleva
Предмет: Обществознание,
автор: ики31